Pengaruh Dukungan Sosial dan Harapan terhadap Kesehatan Mental Selama Pandemi Covid-19 - Kurniawan Dwi Madyo Utomo (Sekolah Tinggi Widya Sasana, 2021)
The restrictions of community activities and isolation are implemented to help restrict the spread of Covid-19. The imposition of these things limits individuals’ access to social support from friends, family, and other social networks. As a consequence, individuals have mental health problems, such as: feelings of loneliness, anxiety, frustration, and depression. Those who are unable to effectively cope with these negative emotions and lack social support are more likely to report higher levels of psychological stress and poor psychological well-being. Therefore, they have to build social support and hope so that they are able to reduce psychological stress and have psychological health during the Covid-19 pandemic.